ChemInform Abstract: Enantioselective Synthesis of cis‐3‐Fluoropiperidin‐4‐ol, a Building Block for Medicinal Chemistry. Issue 6 (11th February 2014) - Shaw, Simon J.; Goff, Dane A.; Boralsky, Luke A.; Irving, Mark; Singh, Rajinder
Abstract Both enantiomers of the title compound (III) are available with high enantioselectivities by using either quinine‐ or quinidine‐derived organocatalyst.